2023
DOI: 10.1371/journal.pbio.3002148
|View full text |Cite
|
Sign up to set email alerts
|

A single-cell atlas of the sexually dimorphic Drosophila foreleg and its sensory organs during development

Abstract: To respond to the world around them, animals rely on the input of a network of sensory organs distributed throughout the body. Distinct classes of sensory organs are specialized for the detection of specific stimuli such as strain, pressure, or taste. The features that underlie this specialization relate both to the neurons that innervate sensory organs and the accessory cells they comprise. To understand the genetic basis of this diversity of cell types, both within and between sensory organs, we performed si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 202 publications
1
9
0
Order By: Relevance
“…Expression of ss was restricted to scale-building cells similar to sv (Figure 3I). Within the same cluster scale-building cell, additional marker genes include CG14395, part of the gene regulatory network (GRN) including shavenbaby/ovo; the gene shavenoid (sha), also found in Hopkins et al (2023). Cluster scale-building cell also expressed genes for transcription factors ichor (ich) and couch potato (cpo), the latter which was also identified in Prakash et al (2024) and we confirmed its expression in scale-building cells by HCR (Figure 3J).…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…Expression of ss was restricted to scale-building cells similar to sv (Figure 3I). Within the same cluster scale-building cell, additional marker genes include CG14395, part of the gene regulatory network (GRN) including shavenbaby/ovo; the gene shavenoid (sha), also found in Hopkins et al (2023). Cluster scale-building cell also expressed genes for transcription factors ichor (ich) and couch potato (cpo), the latter which was also identified in Prakash et al (2024) and we confirmed its expression in scale-building cells by HCR (Figure 3J).…”
Section: Resultssupporting
confidence: 63%
“…Cluster scale-building cell also expressed genes for transcription factors ichor (ich) and couch potato (cpo), the latter which was also identified in Prakash et al (2024) and we confirmed its expression in scale-building cells by HCR (Figure 3J). Cytoskeletal gene quail (qua) and the lncRNA ivory, responsible for the normal development of scale colour, were identified as well (Hopkins et al, 2023;Kittelmann et al, 2018;Livraghi et al, 2024;Prakash et al, 2024). Osiris4 (Osi4), a member of the insect-specific Osiris family of genes recently found to be expressed in a variety of Drosophila macrochaetae, was also restricted to the scale-building cell cluster (Sun et al, 2024).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of single-cell transcriptome studies have been conducted to explore the complexity of insect nervous systems (See Table 1 ). Unlike the peripheral nervous system and sympathetic nervous system, which have received negligible attention with few related publications [ 101 ], the majority of research on insect nervous systems is focused on the central nervous system (CNS).…”
Section: Single-cell Transcriptomics In Insects: Applicationsmentioning
confidence: 99%